where $A=\kappa gkg*/\kappa sks,B=\kappa gkg/\kappa sks$. The following notations are defined in order to express concisely the solution to Eq. (27),Display Formula

(28)$A1=1+A1-A,\u2003\u2003\u2003A2=1-B1-A,\u2003\u2003\u2003A3=1+B1-A,G1=12A1E12(NM-1)-12(NM+1)+A2E1E2-1,G2=-12A1E12(NM+1)+12(NM-1)+A3E1E2,H1=12E1(NM+1)+12(NM-1)E1-NM1E2,H2=-12(NM+1)E1+12(1-NM)1E1+NME2,D2=-12(1+A1E12),\u2003\u2003\u2003\u2003\u2003\u2003F2=-12(E1-1E1),S3=D2H2-F2G2G1H2-G2H1,\u2003\u2003\u2003\u2003\u2003\u2003S4=D2H1-F2G1G1H2-G2H1$